(3GdJhVjM aj TQM ebOeI CHj GddjK GdSeQbfOjs - (3GdMfaj GdbQeGfj, eUdM GdOjf, eUWai Hf RcQjG Hf BjOZeT, (B809 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; (B[ (3GdMeO ddg QH GdYGdejf hGdUdGI hGdSdGe Ydi QShdg eMeO hBdg hYdi LejY QSd Gddg hCfHjGFg hYdi LejY GdedGFcI hCUajGFg hYdi LejY Cgd WGYJgs
(3BNQgG (B:s
(3Efg gh GdhgGH GdaJGM TGcQjf MGeOjf Ydi JeGe GdJhVjM Efg gh GdeTchQ Ydi EaGVI fYeg hGdeSDhd NGJeI GdSYGOI HaVdg hcQegs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 234s
(3eYLe GdeDdajf (B3 / 865s
(3gOjI GdYGQajf (B2 / 433s
(3GdVhA GddGeY (B10 / 160s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs